THE STATE OF DEVELOPMENT OF HEALTH AND RECREATIONAL ACTIVITIES OF THE MUNICIPAL ENTERPRISE “RIVNE REGIONAL WAR VETERANS HOSPITAL” RIVNE REGIONAL COUNCIL - Korotun, S. I.; Burachyk, A. I.; Naprasnikov, S. M. (Rehabilitation and Recreation, 2025)
Purpose. The study is devoted to analyzing the state of development of health and recreational activities of the ME “Rivne Regional War Veterans Hospital” Rivne Regional Council in the context of transfomation processes in the healthcare system of Ukraine and challenges caused by the COVID-19 pandemicand full-scale war.Material. The work uses statistical, financial and economic indicators of the hospital’s activities for 2021–2023. Methods of horizontal and vertical balance sheet analysis, comparative analysis, generalization, systematization and graphical display of data, as well as elements of SWOT analysis, were applied.Results. The hospital, created as a specialized institution for veterans, currently functions as a multidisciplinary medical and rehabilitation center with 240 beds. The analysis showed a sharp increase in the number of treated patients in 2023 – from 2.662 people in 2022 to 5.616 in 2023, which is more than twice the previous figures. The main reasons were post-COVID complications and an increase in the number of combat injuries and neurotraumas. In the therapeutic department, the number of patients increased by 915 people, in the surgical department – by 485, in the anesthesiology and intensive care department – by 41, and in rehabilitation centers – by 1.037 people. In general, the over fulfillment of the bed-day plan in 2023 was 61.2%, which indicates the most efficient use of resources, but at the same time a significant burden on staff. At the same time, the mortality rate decreased to almost zero, which confirms the high professionalism of doctors and the quality of medical services. Financial indicators demonstrate stable revenue growth (from UAH 55.1million in 2021 to UAH 93.2 million in 2023), active attraction of extrabudgetary funds (from UAH 470thousand in 2021 to UAH 9.560.1 thousand in 2023) and significant renewal of the material and technical base. The payroll fund increased by 54% over the period 2021–2023, the average salary increased to UAH12.4 thousand, which has a positive impact on personnel stability. At the same time, capital investments and the cost of fixed assets increased (from UAH 38.9 million in 2021 to UAH 109.8 million in 2023).Conclusions. The study confirms the key role of the hospital as an important element of the regional health system, focused on the medical, psychological and social rehabilitation of veterans and victims.Wartime conditions require increased managerial flexibility, the introduction of modern digital technologies, telemedicine and a system of key performance indicators (KPI). Further development of the hospital shouldbe directed towards expanding the range of health and recreation services, modernizing the infrastructure andimproving the quality of medical care, which will ensure its sustainability and competitiveness in the future.The results of the study can be used to develop strategies for the development of medical institutions in crisis conditions, in particular in regions experiencing humanitarian burden as a result of the war, as well as in the formation of state policy on the rehabilitation of military and civilians.